Pengembangan Sistem Informasi Penggajian Guru Diniyah Berbasis Web: Studi Kasus Dinas Pendidikan dan Kebudayaan Kota Banda Aceh - Rizaldi, Rahmad (Yayasan Kawanad, 2024)
This research aims to design and develop a web-based payroll information system for diniyah teachers at the Education and Culture Office of Banda Aceh City. The problems faced by this institution are payroll processes that still use manual systems, resulting in delays in report provision, salary calculation errors, difficulties in data searching, and lack of transparency in payroll management. The research method used is descriptive method with qualitative approach through observation, interviews, and documentation study. System design uses structured approach with tools such as Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), and flowchart. The research results show that the designed web-based payroll information system can overcome existing problems by providing features such as teacher data management, automatic salary calculation, report generation, and layered security system. This system has structured input design, output design in the form of comprehensive reports and recapitulations, efficient process design, control design that ensures data security, and cost design with total investment of Rp 57,548,000 per year. Implementation of this system can improve operational efficiency, calculation accuracy, management transparency, and user satisfaction. The developed system has flexible architecture and can be integrated with modern technology for further development. The research conclusion shows that web-based payroll information system provides real contribution in public service modernization and improvement of governance quality in education sector.